Kinerja Karyawan Mempengaruhi Lingkungan Kerja dan Komunikasi Karyawan di Grand Inna Kuta Hotel - Meiliana, Ni Putu Karina; Asih, Anak Agung Ketut Sri; Susila, I Made Gede Darma (Jurnal Mosaik Hospitaliti, 2022)
Employees are the main asset that plays an important role in achieving the goals of a company. A supportive work environment and good communication between employees can result in optimal performance. This study aims to obtain empirical evidence of the influence of the work environment and communication on employee performance at the Grand Inna Kuta Hotel. The sample is 62 respondents. This study uses primary data by distributing questionnaires using a Likert scale. The data analysis technique used in this study is a multiple linear regression analysis technique with the SPSS test. The results of hypothesis testing found that the work environment has a positive and significant effect on employee performance, communication has a positive and significant effect on employee performance, work environment and communication simultaneously affect employee performance, and the magnitude of the influence of work environment and communication on employee performance at Grand Inna Kuta Hotel is 45.3%, while the remaining 54.7% is explained by other variables not examined in this study.